Keabsahan Perjanjian dan Tanggung Jawab Badan Hukum Virtual Office terhadap Konsumen yang Melakukan Perbuatan Melawan Hukum - Arsyilla Destriana; Ali Hanafiah (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2020)
AbstractThis thesis aims to establish and clarify the legitimacy of the virtual office lease arrangement because the agreement has violated Article 18 of the Law of the Republic of Indonesia Number of 1999 concerning Consumer Safety because it includes standard provisions and virtual office obligations to customers who perform unlawful actions. This type of study is methodological normative research. Use case studies in the context of legal conduct goods. The main point of the study is the implementation or implementation of positive legal provisions and contracts in fact at any particular legal event that occurs in society in order to achieve predetermined goals. The results showed that the validity of the agreement in the virtual office is the same as the provisions stipulated in Article 1320 of the Civil Code, namely that subjective and objective requirements must be fulfilled. The responsibility of virtual office business entities to consumers who commit acts against the law is to provide all data and information about consumers who commit acts against the law provided that the Virtual office has no errors and can prove that they are not guiltyKeywords: Virtual office, Agreement, Legal Responsibility, Consumer Protection, Standard Clause